2011
DOI: 10.1021/mp100266g
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Peptide Probe for Imaging and Targeted Delivery of Liposomal Doxorubicin to Lung Tumor

Abstract: Targeted delivery of imaging agents and therapeutics to tumors would provide early detection and increased therapeutic efficacy against cancer. Here we have screened a phage-displayed peptide library to identify peptides that selectively bind to lung tumor cells. Evaluation of individual phage clones after screening revealed that a phage clone displaying the CSNIDARAC peptide bound to H460 lung tumor cells at higher extent than other phage clones. The synthetic CSNIDARAC peptide strongly bound to H460 cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Numerous studies have described methods for coating the surface of SPIONs and conjugating targeting ligands [11][12][13][14][15]. In this latter context, various affinity molecules, including antibodies, protein-scaffolds, aptamers and peptides, have been used to achieve cancer-specific targeting after conjugation to a variety of nanoparticles [16][17][18][19][20]. Peptide-based ligands have been of particular interest for such applications because functional groups can be easily introduced at the desired site to achieve site-specific conjugation, and their small size relative to antibodies or aptamers makes it possible to attain a high degree of conjugation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have described methods for coating the surface of SPIONs and conjugating targeting ligands [11][12][13][14][15]. In this latter context, various affinity molecules, including antibodies, protein-scaffolds, aptamers and peptides, have been used to achieve cancer-specific targeting after conjugation to a variety of nanoparticles [16][17][18][19][20]. Peptide-based ligands have been of particular interest for such applications because functional groups can be easily introduced at the desired site to achieve site-specific conjugation, and their small size relative to antibodies or aptamers makes it possible to attain a high degree of conjugation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few other examples of the use of distinct ferrite-based nanoparticles for biomedical applications [43][44][45] (all of them are iron oxide based but also contain another cation, for example, Co +2 or Mn +2 ). In particular, Scarberry et al [46] reported in vivo targeting and extraction of cancer cells by using Co-ferrite-based nanoparticles coated with YSA (Tyr-Ser-Ala) peptide, which binds to the RTK, specifically EphA2 receptors, which are overexpressed in ovarian and other cancer cells. This paper is interesting since it evaluates the possibility of removing metastatic cancer cells from the circulatory system through a magnetic separation (magnetophoresis), which might have an impact on the long-term survival rate of cancer patients.…”
Section: Peptide-nanoparticle Conjugatementioning
confidence: 99%
“…Theranostic liposomal Dox was also studied by Lee and colleagues 47 for the imaging of doxorubicin at and the targeted delivery of doxorubicin to a lung tumor. Lung cancer is the leading cause of death due to cancer, and its high mortality rate appears to be derived from a low therapeutic index for chemotherapy and from late detection due to a lack of sensitive diagnostic biomarkers.…”
Section: Liposomesmentioning
confidence: 99%